Variation in annual periodicity of wood formation in selected tropical rain forest trees with different stem size - Wang, Kang Han (2016)
Knowledge on tropical rainforest tree growth patterns and their response to climate is essential for ecological interpretation. However, detailed information on radial growth dynamics of tropical rain forest trees and its variation with tree size, as well as its climate-growth relationship, is still very limited. Relatively, only a few studies have been done on tropical trees growing in less distinct seasonal climate. Thus, the aim of this research was to investigate the variation of tree growth in response to climatic factors and tree size.Two pioneer tree species (Macaranga gigantea and Endospermum diadenum) and three late-successional tree species (Shorea leprosula, Shorea parvifolia and Shorea acuminata) were selected for this study. All the sampled trees were grown in lowland dipterocarp rainforest of Ayer Hitam Forest Reserve in Selangor, Malaysia. Three methods, which are monthly dendrometer measurement, cambial activity analysis through monthly wood-sampling and knife-cutting method, were applied in this research from March 2013 to March 2014 to determine the radial growth and vessel formation of the sample trees.Results showed that trees with different stem sizes of the same and different species showed different growth patterns at site with similar growing conditions. Total monthly rainfall was not the main factor in determining the radial growth of trees growing in humid forest with less distinct seasonal climate. Meanwhile, cambial activity of the examined species showed periods of active growth that alternate with periods of inactive growth. Sample trees showed species-specific responses during the monitoring period. It is believed that trees with different life forms have different growth strategies and thus react differently to climatic event. Relative humidity and vapour pressure deficit are important factors influencing the cambial activity of late successional species, especially in trees with larger stem size. Sampled trees formed periodical variations of vessel features (vessel frequency and vessel lumen area) based on their stem size besides species-specific response to environmental factors.Additionally, the inconsistency of vessel pattern formation in different stem sizes and life stage suggests that vessel formation can be influenced by other growth factors, in addition to climatic factors. Trees formed more than one cycle in both vessel features and thus showed that the periodicity of vessel features is not necessarily annual.